The Role of Social Media in Promoting Sustainable Brands: Influencing Consumer Perceptions and Behavior Towards Sustainable Products - Sipos, Dario (Technium Sustainability, 2024)
Sustainability has become a primary concern for consumers and businesses, and the need for brands to communicate their environmental initiatives effectively has significantly increased. Social media platforms have become powerful tools for shaping consumer perceptions and behaviors toward sustainable products. This study investigates how social media influences consumer trust, engagement, and purchase intentions related to sustainable brands. The study uses a mixed-method approach that includes qualitative meta-analysis, case studies, and a quantitative online survey. The study examines how transparency, influencer marketing, and consumer engagement on social media impact consumer attitudes and behaviors. Results indicate significant correlations between social media transparency and purchase intentions. According to the study results, influencer credibility is crucial in driving engagement with sustainable products. Case studies of brands such as Patagonia, IKEA, Unilever, and Tesla demonstrate how real-world companies use social media to promote sustainability, which further confirms the relevance of the study's findings.